How Do Immigrants to New Zealand From “Confucian” Societies Conceptualize Social Justice? - Rafie Tehrani, Shahriar (Auckland University of Technology, 2014)
A large group among recent immigrants to New Zealand are from the so called ‘Confucian’ societies and values based on Confucian philosophy may affect their views on social and political issues. The current study examined their perceptions about social justice. Confucianism is the philosophy that has influenced the shaping of East Asian societies with a distinct value system from Western philosophy. In New Zealand, Western philosophy has influenced the shaping of the society as well as how people think about social justice (Duncan, 2004). Dominant modern Western conceptions of social justice revolve around the issue of how to promote the autonomy and freedom of the individual (Duncan, 2004). The ethical value system of Confucianism, on the other hand, does not promote individualism or values such as equality (Chan, 2001). Hence, a Confucian based perspective of social justice may be different to a Western perspective. But, it has been argued that modernity has weakened Confucian based value system in East Asian region (Shin, 2012). This thesis endeavoured to establish if Confucian values influence how immigrants to New Zealand view issues related to social justice by using interviews. In the end, the research found that a Confucian based perceptive of social justice was not present among the participants. The participants in the research believed in certain concepts that cannot be put in line with a Confucian based perspective of social justice. An example of that is the concepts of equality, which is not on line with Confucian based view of social justice.
Keywords: Social justice; Confucianism; New Zealand society; Immigrants; Different values; Equality